Efficient and Reusable Iron Catalyst to Convert CO2 into Valuable Cyclic Carbonates - Ana P. C. Ribeiro; Peter Goodrich; Luísa M. D. R. S. Martins (Molecules, 2021)
The production of cyclic carbonates from CO2 cycloaddition to epoxides, using the C-scorpionate iron(II) complex [FeCl2{κ3-HC(pz)3}] (pz = 1H-pyrazol-1-yl) as a catalyst, is achieved in excellent yields (up to 98%) in a tailor-made ionic liquid (IL) medium under mild conditions (80 °C; 1–8 bar). A favorable synergistic catalytic effect was found in the [FeCl2{κ3-HC(pz)3}]/IL system. Notably, in addition to exhibiting remarkable activity, the catalyst is stable during ten consecutive cycles, the first decrease (11%) on the cyclic carbonate yield being observed during the 11th cycle. The use of C-scorpionate complexes in ionic liquids to afford cyclic carbonates is presented herein for the first time.